Comparison of efficacy of Apacaries gel with various caries removal techniques : An In v itro study - Juntavee, Apa; Peerapattana, Jomji; Nualkaew, Nartsajee; Juntavee, Niwut; Chatrchaiwiwatana, Supaporn; Kaewgham, Sariya; Worawethkanjana, Kanjana; Supanarang, Tongreutai (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to compare the microhardness and residual dentine of deciduous molars after using various mechanical and chemo-mechanical caries removal (CMR) techniques as follow: 1) bur 2) spoon excavator 3) Apacaries gel 4) papain gel 5) papacaries 6) water base gel and 7) control group. The results showed that the dentine hardness after carious removal by Apacaries gel in combination with spoon was not significantly different when compared to Papacaries, papain gel, and bur technique, however, it was significanty different from water base gel, and spoon excavator technique. Chemo-mechanical technique consumed more chair time than bur technique. The scanning electron microscope 1,000 X magnification showed that surface of dentine after carious removal by bur technique seemed relatively smooth, smear layer was detected and the dentinal tubule orifices were plugged. The chemo-mechanical technique (Apacaries gel, Papacaries and water base gel) showed a generalised roughened, flaky surface, and opened orifice of dentinal tubules. The results from this study indicated that Apacaries gel is effective for the CMR treatment for pediatric dental caries in the future.